Analysis of synergistic friction reduction effect on micro-textured cemented carbide surface by laser processing. (November 2022) - He, Chunsheng; Yang, Shucai; Zheng, Minli
Highlights: The optimal geometric shape of the micro-texture is selected through the friction performance analysis. A new method for comprehensive optimization of micro-texture is proposed. The interaction between laser and texture parameters is analyzed. The friction reducing and anti-wear mechanism of the micro-textured surface is analyzed. Abstract: The tribological properties of circular pit, square pit, ring groove micro-textured surface and smooth cemented carbide surface were analyzed by finite element simulation method. Through theoretical analysis and friction and wear test, the tribological properties of circular pits micro-textured (CPMT) cemented carbide surface under the synergistic effect of laser processing parameters and texture arrangement parameters were deeply studied, and the interaction relationship between various influencing factors was developed. Finally, the wear morphology and element distribution of the smooth surface and the CPMT cemented carbide surface were analyzed by SEM. The results show the CPMT surface has better friction performance by comparing with other types of surface micro-textures and smooth surfaces. The laser processing parameters and arrangement parameters of the CPMT are obtained by response surface optimization: laser energy with 1103.494 J/mm 2, scanning speed with 991.2 mm/s, scanning times with 3, and the radial and circumferential distance of the micro-texture with 120 μm and 182 μm, respectively. This paper establishes a systematic preparation process and design theory of surface micro-texture, which provides an important theoretical basis for the further optimization research in the field of micro-textured tools.